2017
DOI: 10.1088/1361-6641/aa98ce
|View full text |Cite
|
Sign up to set email alerts
|

Memristive properties of transparent oxide semiconducting (Ti,Cu)Ox-gradient thin film

Abstract: The paper presents the results of the analysis of memristive properties observed in (Ti,Cu)-oxide thin film with gradient distribution of elements, prepared using the multi-source reactive magnetron co-sputtering process. The performed electrical measurements showed the presence of pinched hysteresis loops in the voltage-current plane for direct and alternating current bipolar periodic signal stimulation. Investigations performed using a transmission electron microscope equipped with an energy dispersive spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Sweeping the current allowed to observe the hysteresis loops, and as one can see in Figure 13 a–c, but the shape of each of the measured curves is distinct. In the case of the structures with (Ti,Co)Ox thin films containing lower Co concentration, a unipolar memristive-like effect can be observed, which is manifested by the memory loop with forward bias polarization ( Figure 13 a) [ 38 , 39 ]. The occurrence of such effects has not been reported so far in the case of TiO 2 coatings with the addition of Co. Usually, for these types of thin-film materials, a linear relationship between current and voltage is usually observed [ 15 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sweeping the current allowed to observe the hysteresis loops, and as one can see in Figure 13 a–c, but the shape of each of the measured curves is distinct. In the case of the structures with (Ti,Co)Ox thin films containing lower Co concentration, a unipolar memristive-like effect can be observed, which is manifested by the memory loop with forward bias polarization ( Figure 13 a) [ 38 , 39 ]. The occurrence of such effects has not been reported so far in the case of TiO 2 coatings with the addition of Co. Usually, for these types of thin-film materials, a linear relationship between current and voltage is usually observed [ 15 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The deposition system and the method for the preparation of gradient thin films have already been described in detail in [41][42][43][44][45]. The thin films were deposited via reactive magnetron co-sputtering, using two circular titanium targets (99.995%) and one circular copper target (99.995%).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous works [ 41 42 ] have shown that an interesting alternative to the well-known conventional structures, with a multilayer stack of thin films with different electrical conducting and nonconducting properties described above, could be a thin film the composition of which changes along its thickness. So far, a memristive-like memory effect has been observed for thin film structures with a so-called V-type [ 41 ] or linear [ 42 ] gradient profile of the Cu distribution in (Ti–Cu)Ox thin films. In the present paper, the results for (Ti–Cu) oxide semiconducting thin films prepared with a U-shape distribution profile of copper are presented.…”
Section: Introductionmentioning
confidence: 99%
“…The deposition system and the method for the preparation of gradient thin films with different profiles of element concentration have already been described in detail in [44][45][46][47][48] . The thin films were deposited in a reactive mode in the magnetron co-sputtering process, using two circular titanium targets (99.995%) and one circular copper target (99.995%).…”
Section: Methodsmentioning
confidence: 99%